Simulation Study of DC Fast-Charging Electric Vehicles - Mohd Akbal, Muhammad Irfan; Razali, Muhammad Anas (Evolution in Electrical and Electronic Engineering, 2023)
Electric Vehicles (EVs) are promising individual means of transportation in the future, providing local emissions-free, quiet, resource-flexible mobility. However, there is a weakness of EV where it’s the recharging time of EV. This study proves charging time of EVs can fully recharge in less than 30 minutes. This simulation study was performed using MATLAB Simulink version 2022a with a battery capacity of 75kWh. The method applied for this study is recharging using the constant voltage (CV) technique and using a Simulink block. The supply source for MATLAB Simulink uses using three-phase source. To observe the charging time of a DC Fast Charging Electric Vehicle Battery, perform less than 30 minutes. Accordingly, this simulation study proves the time of recharging an EV battery.